2011
DOI: 10.1016/j.bpj.2011.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Constraints on the Force-Dependent Growth of Focal Adhesions

Abstract: Focal adhesions (FAs) are the predominant mechanism by which cells mechanically couple to and exert traction forces on their extracellular matrix (ECM). It is widely presumed that FA size is modulated by force to mediate changes in adhesion strength at different levels of cellular tension. However, previous studies seeking correlations between force and FA morphology have yielded variable and often conflicting results. Here we show that a strong correlation between adhesion size and traction force exists only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

35
187
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(224 citation statements)
references
References 50 publications
35
187
1
1
Order By: Relevance
“…S2. Furthermore, such assemblies are mostly distributed at the cell periphery (18,19), as shown in Fig. 1A.…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…S2. Furthermore, such assemblies are mostly distributed at the cell periphery (18,19), as shown in Fig. 1A.…”
Section: Methodsmentioning
confidence: 93%
“…The FA band is treated as an elastic plaque representing the stiffness of the constituent molecules (with Young's modulus E p ) connected to the ECM through an array of integrins (modeled as springs with stiffness k i ) whose density (ϕ i ) is assumed to be proportional to the fiber density (ϕ f ) underneath the cell. Although more complicated models with strain-dependent detachment rates can be used for integrins, recent experiments have shown that a simple description (i.e., treating the integrin as a linear spring) can capture the response of integrins sufficiently because the timescale for integrin binding dynamics [i.e., a few seconds (9,20)] is much shorter than that for FA growth [i.e., a few minutes (18)]. In addition, the proximal end of the band is connected to the cell nucleus through stress fibers (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, recent modeling (18) as well as indirect observations (19,20) suggest that the contractile actomyosin apparatus can act as a global rigidity sensor (21). From a physical point of view, the deformation of the surrounding matrix in response to cell contractility is poorly understood; plausible mechanisms of cell mechanosensitivity imply that the regulation could be either mediated by the stress exerted by cells, or by the strain in the ECM (7,(22)(23)(24). These intriguing questions are currently intensively debated, because the detailed mechanisms of force transduction in response to ECM might explain the observed discrepancies in adhesion (1, 25), migration (2, 26), and differentiation (3, 27) of cells in environments of different rigidities and over different time scales.…”
mentioning
confidence: 99%
“…This, in concert with focal adhesion kinase (FAK), Src and other signalling modules controlled via integrin ligation, directs focal adhesion (FA) assembly and maturation 19 . Importantly, such assembly processes are regulated by mechanical force [20][21][22] . In particular, nascent complexes, including scaffolding molecules such as paxillin (Pxn), form at the leading edge, while myosin II-mediated tension leads to recruitment and activation of accessory proteins, promoting growth of the complex distal to the leading edge 23 .…”
mentioning
confidence: 99%